7-Eleven Inc. : the fine line between franchise independence and interdependence - Hunt, Terrell, (SAGE Business Cases., 2019)
On June 17, 2013, federal agents from the Immigration and Customs Enforcement Agency (ICE) seized fourteen 7-Eleven franchised stores that were responsible for running what the authorities described as a "modern day plantation" ring. The owners of these franchises were suspected of recruiting more than 50 illegal immigrants, working those employees approximately 100 hours a week, siphoning their pay, and forcing them to live in "unregulated boarding houses." The case focuses on 7-Eleven Inc.'s response and how the company sought to distance itself from individual franchise holders.